A Defence of the Traditional Chronology of 542–545, Again - Michael Whitby (Classica Cracoviensia, 2023)
The chronology of the campaigns of the years 542–545 has been the subject of debate, with Michael Whitby defending the traditional interpretation that Procopius’ long account of the bubonic plague concealed the end of the year 542, whereas Geoffrey Greatrex has championed the chronology of Kislinger and Stathakopoulos, which locates Khusro’s march to Adarbiganon and the Roman defeat at Anglon in late 542 and the siege of Edessa in 543, with Procopius failing to note the end of a year during peace negotiations in 544–545. Considerations of the progress of Khusro I’s invasion in 542 in light of his probable speed of march, and the distances he had to cover, coupled with the relatively slow advance of bubonic plague over large land masses and Procopius’ practice in arranging his material, point to the missing year-end, being that of 542/543. While the new chronology cannot absolutely be ruled out, the assumptions on which it is based are shaky.